Analysis of The Effectiveness of Earned Value Method In Road Widening Project Management In Mojokerto Regency - Sugeng Hariyadi; Hanie Teki Tjendani; Budi Witjaksana (Pelopor Publikasi Akademika, 2024)
In construction project management, achieving three main goals, namely cost, quality, and time, becomes the primary focus. This study aims to evaluate a road widening project in Mojokerto Regency with a target completion time of 150 days. To prevent delays and cost overruns, researchers adopted the Earned Value method as a tool to identify early warnings regarding project performance. This method integrates cost and time measurements through indicators such as Cost Variance (CV), Schedule Variance (SV), Cost Performance Index (CPI), Schedule Performance Index (SPI), Estimated at Completion (EAC), and Estimated Schedule at Completion (EAC). The analysis results show that the additional costs required (ETC) amounted to Rp 3,276,704,110.14, with an estimated additional time (ETS) up to the 12th week being 87 days. The project's cost change (EAC) reached Rp 3,961,767,811.01 from the contract cost, while the estimated project completion time (EAS) was 171 days. These findings indicate that the construction service provider has implemented an efficient execution method with consistent monitoring, ensuring the smooth progress of the project.